Penerapan Penerapan Media Aplikasi OME TV Dalam Pembelajaran Bahasa Indonesia Bagi Penutur Asing (BIPA) - Cici, Annisa Cici Khoirala; Della, Della Amadiah; Diera, Diera Elika Purba; Safinatul Hasanah Harahap (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to describe the results of implementing the Ome Tv media application in learning Indonesian for Foreign Speakers (BIPA). BIPA learning has a big problem, namely student learning motivation. A boring class atmosphere is one of the reasons students are not motivated to study BIPA. Generating learning motivation among BIPA students aged teenagers and early adults is by providing something extraordinary and new in BIPA learning. The method used in this research is descriptive qualitative research using a case study approach. The results of this research indicate that the Ome Tv application media can be used to achieve these learning objectives efficiently. The Ome Tv media application is able to deliver listening, speaking, reading and grammar courses in BIPA learning. This can provide fun learning in the classroom. The Ome Tv application is not only interesting and entertaining for students, but there are many reasons to use it in BIPA learning.